Evliliği Sorgularken: Levayih-i Hayat - (:unkn) unknown (My University, 2005)
19. yy dünyada özellikle de Avrupa ve Amerika'da kadının konumunu sorguladığı ve bağımsızlığını aradığı bir dönüm noktasıdır. Osmanlı toplumunda da Batı medeniyetinin yeni kavram ve değerleri ile karşılaşan kadın değişmeye başlar. Levâyih-i Hayat'ta (1897) ilk kadın romancılarımızdan Fatma Aliye Hanım farklı evlilik tanımlan çerçevesinde Osmanlı toplumundaki kadm-evlilik ilişkisini inceler. 19. yüzyılda bir aydın kadın yazarın gözlemlerini aktaran romandaki evlilik tanımları ve kadın- evlilik ilişkisinin günümüzde de benzer özellikler göstermesi eseri 21. yüzyılda da güncel kılmaktadır.

In the world, especially in Europe and the USA, the 19th century is an important period for the emancipation of the women. In this period the ottoman woman in front of the European ideas, concepts and standards of judgement also began to change. This change appears in the social life particulary in the family structure and life. Fatma Aliye, the famous novelist of the Tanzimat period, in her novel named "Levâyih-i Hayat" (Scenes of the life) describes and analyses the marriage life with different critical descriptions from an intellectual woman writer's point of view. What makes this novel worth mentioning and bringing out at the beginning of the 21s' century is the similarities of the feminine experience in the marriage between the 19th and the 21st centuries.
A Critical Approach the Marriage: Levayih-i Hayat
Keywords: Kültürel Çalışmalar; Tarih; Beşeri Bilimler; Sosyal Çalışma